Decatungstate Photocatalyzed Acylations and Alkylations in Flow via Hydrogen Atom Transfer. Issue 16 (6th November 2015) - Bonassi, Filippo; Ravelli, Davide; Protti, Stefano; Fagnoni, Maurizio
Abstract: A set of atom‐economical radical conjugate addition reactions of alkyl and acyl radicals onto electron‐poor olefins or diisopropyl azodicarboxylate has been carried out on a multi‐gram scale under continuous flow conditions. The process is based on the use of the inorganic photocatalyst tetrabutylammonium decatungstate (TBADT), which is capable to activate selectively a variety of CH bonds in different substrates, including aldehydes, amides, ethers and alkanes. A wide range of synthetic targets has been synthesized according to this procedure, including 1, 4‐difunctionalized derivatives (e.g., 1, 4‐diketones or keto esters). All the reactions have been carried out in a meso ‐scale flow photoreactor consisting in coils of UV‐transparent FEP tubing (fluorinated ethylene propylene) wrapped around a water‐cooled 500 W medium pressure mercury vapor lamp. The use of such a photochemical apparatus caused a reduction of the residence time, a notable increase of the STY (space time yield) and of the productivity values with respect to those measured for the corresponding batch processes, often leading to an improvement of the overall sustainability of the process (process mass intensity – PMI – values down to 10 kg kg −1 ). Abstract :